AUTHORITY OF EAST JAVA PROVINCE INSPECTORATE IN PREVENTING CRIMINAL ACTS OF CORRUPTION IN EAST JAVA PROVINCE GOVERNMENT - Bramanto Wisynu Wardhana; V. Rudi Handoko; Achluddin Ibnu Rochim (DIA: Jurnal Administrasi Publik, 2023)
This study aims to determine the constraints on the authority of the Inspectorate of East Java Province in preventing criminal acts of corruption within the East Java Provincial Government, using normative legal research methods that are analytical descriptive. The results of the research show that the authority of the Provincial Inspectorate which has been regulated in laws and regulations needs to be revised to strengthen the position of the Inspectorate in its authority to prevent acts of corruption in the Regional Government. Changes to laws and regulations are the main thing that needs to be revised because the position of the Provincial Inspectorate is currently still under the Provincial Secretary. Inspectors in districts/cities must be appointed by the Head of Province (Governor) through the Pansel and Provincial Inspectorates appointed by the Minister of Home Affairs. With this more tiered authority, the inspectorate will become an independent institution and can prevent corruption from occurring in its area without fear of being arrested by the regional head.